Reflexos dos parâmetros de avaliação utilizados na recepção sobre a qualidade da semente de soja - Brisolara, Cristiane Velleda (2009)
Analysis of data referring to the tests made on reception of soybean seed harvested on Cereal Ouro farms, a company originally from Rio Grande do Sul, currently installed in Rio Verde/Goiás, during 2007/2008 crop, in order to analyze through the results of the tests conducted by the internal quality control (CIQ), the importance of establishing evaluation parameters used at the reception on the quality of soybean seed lots. The CIQ, an important tool of the company, helps to identify problems and its possible causes and, in decision making, reducing large-scale risks at any stage of the production, since it generated information about the performance potential of the seeds. The evaluations about the quality of soybean seed received in seed processing unit (UBS) included tests of percentage of moisture, percentage of mechanical damage (by testing sodium hypochlorite), percentage of broken seeds, percentage of green seed by sieve size and vigor, and viability, by tetrazolium test. The results were compared to tests done after the formation of the lots, which passed by germination, emergence in sand and tetrazolium tests. Concluding that there is a tendency of soybean seeds maintain high quality during the storage, showing that the quality standards adopted on reception must be strict.